2013
DOI: 10.14256/jce.871.2013
|View full text |Cite
|
Sign up to set email alerts
|

Pozzolanic mortars for the conservation of old masonry structures

Abstract: Pozzolanic mortars for the conservation of old masonry structures The design of repair mortars started from the characterization of the original mortar samples preserved in small areas in the floors of the Dungeon Tower, Bač Fortress. Two materials (waste brick and clay material) were investigated in order to select the pozzolanic material which later was a component of the repair mortar. Based on the compatibility test of the examined old mortars and of the newly developed mortars, slaked lime based, the mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…During the carbonation/hydration process, a contact zone without cracks was formed between the original (HM) and the new (MM) sample. The morphology investigation, as shown in Figure 5 , of the contact zone showed that the formed area had a satisfactory appearance (without cracks) [ 6 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…During the carbonation/hydration process, a contact zone without cracks was formed between the original (HM) and the new (MM) sample. The morphology investigation, as shown in Figure 5 , of the contact zone showed that the formed area had a satisfactory appearance (without cracks) [ 6 , 21 ].…”
Section: Resultsmentioning
confidence: 99%